PRICE STRUCTURE PRODUCTS - Yu. A. Kropin (Финансы: теория и практика, 2017)
Article Retracted.The peculiarity of the current state of economic science is that it has little interest in, and often deliberately evades a study of many aspects of the deep nature of the market and individual market phenomenon. One of these phenomena is the structure of the prices of goods which are at the basis of the structure of earnings of participants of market relations, based on the structure of the gross national product. The purpose of research — to argue a new approach to the structure. The research problem— to reveal the author’s view on the structure of the price of goods. In disclosing the author’s view of the structure of the price of the goods has been used the dialectical method of transformation of quantity into a new quality, as well as the law of dialectics, which states that the whole is not reduced to the simple sum of its parts, the whole is more than the simple sum of its components to «some value». As a result of the study it was concluded that the structure of the price of goods includes the addition of more cost price of new consumer properties of the produced commodity product.